Entrepreneurial Intention and Outcome Expectancy: Evidence from South Korea and China - Jiang, Zhou; Wang, Zhongmin (Contemporary Management Research, 2014)
Focusing on the East Asian context, this study examines (1) cultural and gender differences in entrepreneurial intention, (2) the mediating effects of culture and gender on the relationships between entrepreneurial intention and expectancies of positive entrepreneurial outcomes, and (3) the results of entrepreneurial intention of females. The findings reveal that while Chinese students have a greater entrepreneurial intention than South Korean students, the relationships between entrepreneurial intention and outcome expectancies are stronger in South Korean than in Chinese students. In terms of gender, males have a greater entrepreneurial intention than females. The relationships between entrepreneurial intention and outcome expectancies are stronger in male than in female students. Social status and self-realization are the entrepreneurial outcomes that females value most.Keywords: Entrepreneurial Intention, Desired Entrepreneurial Outcomes, Cultural Difference, Gender DifferenceTo cite this document: Zhou Jiang and Zhongmin Wang, "Entrepreneurial Intention and Outcome Expectancy: Evidence from South Korea and China", Contemporary Management Research, Vol.10, No.3, pp.251-270, 2014.Permanent link to this document:http://dx.doi.org/10.7903/cmr.12012